2016
DOI: 10.1016/j.ssresearch.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The stigma of mental illness in the labor market

Abstract: Mental illness labels are accompanied by devaluation and discrimination. We extend research on reactions to mental illness by utilizing a field experiment (N = 635) to test effects of mental illness labels on labor market discrimination. This study involved sending fictitious applications to job listings, some applications indicating a history of mental illness and some indicating a history of physical injury. In line with research indicating that mental illness leads to stigma, we predicted fewer callbacks to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(101 citation statements)
references
References 41 publications
7
91
2
1
Order By: Relevance
“…42 Furthermore, the processes examined by SCT researchers that have demonstrated inequality based on attributes such as gender or mental illness are reflected in more macro studies demonstrating factors such as the gender wage gap or mental illness hiring discrimination. 43 However, our study does not account for other factors that may impact interactions in real-world settings. For example, it might be the case that the public associates veterans with characteristics we did not or could not address in our experimental design.…”
Section: Resultsmentioning
confidence: 99%
“…42 Furthermore, the processes examined by SCT researchers that have demonstrated inequality based on attributes such as gender or mental illness are reflected in more macro studies demonstrating factors such as the gender wage gap or mental illness hiring discrimination. 43 However, our study does not account for other factors that may impact interactions in real-world settings. For example, it might be the case that the public associates veterans with characteristics we did not or could not address in our experimental design.…”
Section: Resultsmentioning
confidence: 99%
“…Participant responses suggested that allies have to work within practical constraints, seizing opportunities by corralling resources when they can, while at the same time advocating for the positions at multiple levels and across a range of settings. The stigma associated with mental illness further impacts on the perceived credibility of consumer researchers (Ghisoni et al., ; Hipes, Lucas, Phelan, & White, ; Segal & Hayes, ). Allies, on the other hand, are seen as credible due to their positions, professional background and research track record (Happell & Scholz, ; Hutchison, ).…”
Section: Discussionmentioning
confidence: 99%
“…; Ipes et al . ). The current findings challenge such dominant ideas and suggest that systemic issues pose much more formidable barriers.…”
Section: Discussionmentioning
confidence: 97%